The Relationship between Democratic Parenting Style and School Readiness among First-grade Students: Hubungan antara Gaya Pengasuhan Demokratis dan Kesiapan Bersekolah di Kalangan Siswa Kelas 1 SD - Izza, Niswatul; Mariyati, Lely Ika (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study investigates the relationship between democratic parenting style and school readiness among first-grade students at SD Negeri Sidokare 2 Sidoarjo. The research aims to examine whether a correlation exists between the two variables. Data were collected through questionnaires and the Nijmeegse Schoolbekwaamheids Test (NST). The sample comprised 66 students selected using accidental sampling. The data analysis involved Pearson's product-moment correlation coefficient in SPSS 26.0. The results indicate a significant positive correlation (rxy = 0.662, p = 0.000) between democratic parenting style and school readiness. Higher levels of democratic parenting style correspond to higher levels of school readiness among first-grade students. These findings imply that parents who adopt a democratic parenting style contribute to their children's preparedness for elementary school. The study suggests that schools provide training on the importance of parenting styles, particularly democratic parenting, to foster children's potential as they enter elementary school. Highlight: Positive correlation: The study reveals a significant positive correlation (rxy = 0.662, p = 0.000) between democratic parenting style and school readiness among first-grade students. Impact of democratic parenting: Higher levels of democratic parenting style are associated with higher levels of school readiness among children entering elementary school. Implications for schools and parents: The findings emphasize the importance of implementing democratic parenting styles to foster children's readiness for school. Schools should provide training to parents on the benefits of democratic parenting to optimize children's potential as they transition to elementary school. Keyword: Democratic Parenting Style, School Readiness, First-Grade Students, Correlation, Quantitative Study